DEVELOPING SUPPLEMENTARY READING MATERIALS FOR SENIOR HIGH SCHOOL STUDENTS IN ENGLISH COURSE PROGRAM - Devilia Indah Kusuma (Language-Edu, 2020)
In accordance with the successfulness of school examination, every school has its own way to pass the completion. Additional program is added to be the solution in preparing students become more ready to face the school examination. The provided book in this program is only consist of some exercises without summary or brief theory about each material. Another problem is that students are forced to learn the material independently because of the limited time in each session. It is difficult for them to understand the material by using only exercise book. From those problems, it is important to develop product which support the provided book in English course program. The development of this product is based on students’ need and interest and it is categorized as Research and Development (R&D) since the objective of this study is to develop a product which can be applied for an educational program in English learning and teaching. The final product of this development is supplementary reading materials entitled “Smart Reading. Question Bank”. The material is about types of text. This product is designed colourfully with attractive pictures illustration in order to make students become more interested in doing the exercises.Keywords: developing, supplementary reading materials, English course program